2012
DOI: 10.1111/j.1471-0307.2012.00842.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical, textural and sensorial changes during the ripening of Majorero goat cheese

Abstract: Majorero cheeses from six producers were analysed for basic physicochemical, textural, colour and sensorial characteristics. These analyses took place at different stages of the ripening process, from 15 to 90 days. The basic composition and the texture attributes of Majorero cheese changed significantly during the storage period (P < 0.001). Fracturability, hardness, adhesiveness and gumminess increased from 15 to 90 days of ripening while elasticity decreased. Furthermore, ripening time affected most of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
34
2
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 24 publications
14
34
2
4
Order By: Relevance
“…On the contrary, some other authors did not perceive any changes over the whole period of ripening . The fat/TS content values found in our study were similar to those reported for Murcia al Vino cheese ) but higher than those in cheeses made in the Canary Islands (Fresno and Alvarez 2012;Peláez Puerto et al 2004;Sanchez-Macias et al 2010). Finally, the NaCl levels (1.3 for fresh and 2.0 for semihard and hard cheeses, respectively) are within the range of other Andalusian cheeses (Fernández-Salguero and Gómez Díaz 1997) and other Spanish goat's milk cheeses (Mas et al 2002;Tejada et al 2008).…”
Section: Physicochemical Characterizationsupporting
confidence: 78%
See 3 more Smart Citations
“…On the contrary, some other authors did not perceive any changes over the whole period of ripening . The fat/TS content values found in our study were similar to those reported for Murcia al Vino cheese ) but higher than those in cheeses made in the Canary Islands (Fresno and Alvarez 2012;Peláez Puerto et al 2004;Sanchez-Macias et al 2010). Finally, the NaCl levels (1.3 for fresh and 2.0 for semihard and hard cheeses, respectively) are within the range of other Andalusian cheeses (Fernández-Salguero and Gómez Díaz 1997) and other Spanish goat's milk cheeses (Mas et al 2002;Tejada et al 2008).…”
Section: Physicochemical Characterizationsupporting
confidence: 78%
“…These pH fluctuations were also observed by other researchers, who reported a significant decrease in pH in the first 15 days of ripening that continued, although it was less pronounced, until the 30th day of ripening and then it showed a slight increase in 60-and 90-day-old cheeses (Alvarez et al 2007). The pH values obtained in our study were close to the range of values observed by different authors for other goat's milk cheeses manufactured in Andalusia (Fernández-Salguero and Gómez Díaz 1997) and in other regions of Spain (Fresno and Alvarez 2012;Fresno et al 2011;Gonzalez-Fandos et al 2000;Peláez Puerto et al 2004;Tejada et al 2008). The results obtained for fat and TS contents showed a tendency for their values to increase over the ripening period (p<0.05).…”
Section: Physicochemical Characterizationsupporting
confidence: 72%
See 2 more Smart Citations
“…In the same way, texture attributes were modified, increasing their hardness due to a loss of moisture (Cabezas et al ., ; Tejada et al ., ; Fresno & Alvarez, ; García et al ., ) and reducing their elasticity (Fresno & Alvarez, ) and solubility (García et al ., ). With regard to granularity, different authors observed a slight increase in grain size as the ripening advanced (Tejada et al ., ; Fresno & Alvarez, ; García et al ., ), that was not seen in our study.…”
Section: Resultsmentioning
confidence: 99%